2018
DOI: 10.1186/s12959-018-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

COSIMO – patients with active cancer changing to rivaroxaban for the treatment and prevention of recurrent venous thromboembolism: a non-interventional study

Abstract: BackgroundAround 20% of venous thromboembolism (VTE) cases occur in patients with cancer. Current guidelines recommend low molecular weight heparin (LMWH) as the preferred anticoagulant for VTE treatment. However, some guidelines state that vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs) are acceptable alternatives for long-term therapy in some patients if LMWHs are not available. LMWHs and VKAs have a number of drawbacks that can increase the burden on patients. DOACs, such as rivaroxaban,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…COSIMO registry will include DDI as a secondary outcome. 42 A prospective, observational, and hypothesis-generating international registry from the Internal Society of Thrombosis and Hemostasis (ISTH) 43 was designed to assess the safety and efficacy of 200 patients with cancer followed for 6 months on concomitant use of DOACs and antineoplastic and supportive care drugs. Targeted therapies include ibrutinib, acalabrutinib, imatinib, nilotinib, osimertinib, alectinib, sunitinib, cabozantinib, lapatinib, palbocyclib, vemurafenib, or everolimus.…”
Section: Discussionmentioning
confidence: 99%
“…COSIMO registry will include DDI as a secondary outcome. 42 A prospective, observational, and hypothesis-generating international registry from the Internal Society of Thrombosis and Hemostasis (ISTH) 43 was designed to assess the safety and efficacy of 200 patients with cancer followed for 6 months on concomitant use of DOACs and antineoplastic and supportive care drugs. Targeted therapies include ibrutinib, acalabrutinib, imatinib, nilotinib, osimertinib, alectinib, sunitinib, cabozantinib, lapatinib, palbocyclib, vemurafenib, or everolimus.…”
Section: Discussionmentioning
confidence: 99%
“…However, real‐world evidence on patient satisfaction with, or preferences for, DOACs in patients with CAT were lacking. The CALLISTO program was developed with an RCT (COSIMO) and a real‐world study (CONKO‐011) to collect data on patient‐reported treatment satisfaction as a primary objective . The recent results from COSIMO were mentioned in section 3.…”
Section: Ongoing Studies In the Callisto Programmentioning
confidence: 99%
“…The recent results from COSIMO were mentioned in section 3. The phase III clinical trial CONKO‐011 will compare patient‐reported treatment satisfaction in patients after randomization to rivaroxaban or LMWH therapy . Quality of life will be measured using the Spitzer index, ACTS, and the treatment satisfaction questionnaire for medication.…”
Section: Ongoing Studies In the Callisto Programmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compared with LMWH, rivaroxaban was associated with significantly lower rates of recurrent VTE (11.9 versus 14.7% at 12 months; hazard ratio 0.83; 95% CI 0.73–0.96; P = 0.01) and similar rates of major bleeding (the latter of which was identified using the Cunningham algorithm) [60]. COSIMO, an ongoing noninterventional, observational study that is part of the CALLISTO programme, will provide data on patient-reported outcomes and treatment satisfaction in patients with cancer-associated thrombosis switching to rivaroxaban therapy after at least 4 weeks’ treatment with standard anticoagulation (LMWH/VKA) [61].…”
Section: Rivaroxaban For the Treatment Of Venous Thromboembolism In Amentioning
confidence: 99%